The politics of deregulation - Derthick, Martha (Brookings Institution, 1985)
The standard wisdom among political scientists has been that ""iron triangles"" operated among regulatory agencies, the regulated industries, and members of Congress, all presumably with a stake in preserving regulation that protected the industries from competition. Despite almost unanimous agreement among economists that such regulation was inefficient, it seemed highly unlikely that deregulation could occur. Yet between 1975 and 1980 major deregulatory changes that strongly favored competition did take place in a wide range of industries. The results are familiar to airline passengers, user.